2001
DOI: 10.1007/s001090000176
|View full text |Cite
|
Sign up to set email alerts
|

Natural zeolite clinoptilolite: new adjuvant in anticancer therapy

Abstract: Natural silicate materials, including zeolite clinoptilolite, have been shown to exhibit diverse biological activities and have been used successfully as a vaccine adjuvant and for the treatment of diarrhea. We report a novel use of finely ground clinoptilolite as a potential adjuvant in anticancer therapy. Clinoptilolite treatment of mice and dogs suffering from a variety of tumor types led to improvement in the overall health status, prolongation of life-span, and decrease in tumors size. Local application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 18 publications
5
172
0
7
Order By: Relevance
“…Other possible reasons for the inhibition of cancer cell proliferation with zeolite treatment might due to its effect on cancer cell signaling pathways, or possibility of weak interactions such as van-der Waals, hydrogen bonding, electrostatic interactions between zeolite and some protein like structures in cell culture media (such as aminoacids, or growth hormones secreted by the cells) due to zeolite's ion exchange and adsorptive properties. Similar cases were suggested previously [21,43]. It was reported that decrease in the viability of the tumor cells with the zeolite treatment might be due to adsorption of some serum components such as epidermal growth factor (EGF) by the clinoptilolite.…”
Section: Cytotoxicity Results For Caco-2 Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…Other possible reasons for the inhibition of cancer cell proliferation with zeolite treatment might due to its effect on cancer cell signaling pathways, or possibility of weak interactions such as van-der Waals, hydrogen bonding, electrostatic interactions between zeolite and some protein like structures in cell culture media (such as aminoacids, or growth hormones secreted by the cells) due to zeolite's ion exchange and adsorptive properties. Similar cases were suggested previously [21,43]. It was reported that decrease in the viability of the tumor cells with the zeolite treatment might be due to adsorption of some serum components such as epidermal growth factor (EGF) by the clinoptilolite.…”
Section: Cytotoxicity Results For Caco-2 Cellssupporting
confidence: 81%
“…Purified natural clinoptilolite was reported to be harmless to the human body [17] and was used as antidiarrheaic drug [18] and as antiacid agent for humans suffering from the hyperacidity without showing any toxic or biological hazard [19,20]. A novel use of micronized clinoptilolite as a potential adjuvant in anticancer therapy was reported [21]. It was used in anticancer treatment of mice and dogs suffering from cancer and it resulted prolonged of life span and improvement of health status.…”
Section: Introductionmentioning
confidence: 99%
“…Clinoptilolites have shown antioxydative and anticancer effects [39][40][41]. They support the immune activity [20,42,43] note that clinoptilolite with low toxicity and high adsorption capacity toward Pb 2+ in a strong acid solution has a potentiality for application in the life sciences.…”
mentioning
confidence: 91%
“…The isomorphic substitution of Si 4+ by Al 3+ causes a negative charge which is compensated by exchangeable cations such as Na . Due to its unique adsorption, cation exchange, catalytic, hydration and dehydration properties, clinoptilolite rich mineral specimen has been proposed for ammonium (Huang et al, 2010;Karapınar, 2009;Şenatalar and Sirkecioğlu, 1995;Ülkü, 1984) and heavy metal removal (Can et al, 2010;Motsi et al, 2009;Top and Ülkü, 2004), animal nutrition (Mumpton, 1999), gas adsorption (Armenta et al, 2003;Faghihian et al, 2008;Özkan and Ülkü, 2005), building and polymer industry (Atakul et al, 2005;Demir et al, 2008;Erdoğan et al, 2008;Savrık et al, 2010), as well as for biomedical applications (Pavelic et al, 2001(Pavelic et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%